Individuality in the Interchangeable Use of Punctuation - Xayrulloyeva, Gulasal (Центр Научных Публикаций (buxdu.uz), 2023)
The article discusses how certain punctuation marks in Uzbek have synonymous relationships, meaning that one mark can be used in place of another in a text. It presents an argument about the proper use and function of punctuation marks, and how they are closely linked to the syntax of the language. The article provides factual examples to illustrate that while there is a practice of substituting one punctuation mark for another, this approach may not always yield the intended effect.